2016
DOI: 10.3892/ol.2016.5177
|View full text |Cite
|
Sign up to set email alerts
|

Metaplastic carcinoma of the breast: Imaging and pathological features

Abstract: Abstract. Metaplastic carcinoma of the breast is a rare form of breast cancer. The aim of the present study was to investigate the imaging and pathological features of metaplastic carcinoma. The features identified on mammography and sonography were retrospectively reviewed in 13 women with metaplastic carcinoma of the breast. The results from the mammographs and sonographs were additionally evaluated using immunohistochemical staining for the expression of the estrogen receptor (ER) and progesterone receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 12 publications
5
24
1
Order By: Relevance
“…However, MCB have been described as presenting at a younger age, with larger tumor size and a more rapid growth than the more prevalent forms of breast cancer [ 1 2 8 10 ]. Nevertheless, some authors have found that MCB can be more common in women older than 50 years, such as in this series that has a median age of 65 years at presentation [ 4 13 ].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…However, MCB have been described as presenting at a younger age, with larger tumor size and a more rapid growth than the more prevalent forms of breast cancer [ 1 2 8 10 ]. Nevertheless, some authors have found that MCB can be more common in women older than 50 years, such as in this series that has a median age of 65 years at presentation [ 4 13 ].…”
Section: Discussionmentioning
confidence: 94%
“…The most frequent clinical finding of MCB is a palpable breast mass, similar to the more common forms of breast cancer [ 1 2 4 ]. However, MCB have been described as presenting at a younger age, with larger tumor size and a more rapid growth than the more prevalent forms of breast cancer [ 1 2 8 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to WHO classification 2012, MBCs are classified as metaplastic carcinoma of no special type, low-grade adenosquamous carcinoma, fibromatosis like carcinoma, squamous cell carcinoma, spindle cell carcinoma, metaplastic carcinoma with mesenchymal differentiation (chondroid differentiation, osseous differentiation), mixed metaplastic carcinoma and myoepithelial carcinoma 12–14. The most common type of MBC is squamous cell carcinoma accounting for 0.5%–3.7% of all the breast cancers followed by spindle cell carcinoma and matrix-producing carcinoma 14. The main pathological feature of this cancer is epithelial and mesenchymal transition 15 16.…”
Section: Discussionmentioning
confidence: 99%